Economic policy uncertainty and corporate financialization: Evidence from China - Zhao, Yan; Su, Kun (International review of financial analysis, 2022)
Using a quarterly sample of Chinese non-financial listed firms from 2007 to 2020, we find a U-shaped relationship between economic policy uncertainty (EPU) and corporate financialization. When economic policy uncertainty (EPU) is in an appropriate range, the increase of economic policy uncertainty (EPU) is unlikely to make firms increase financial assets investment. In contrast, the operational risk induced by too high economic policy uncertainty (EPU) will make firms more willing to invest in financial assets. Additionally, we show that the effect is more noticeable when firms are non-state-owned, have lower financing constraints, or are located in lower marketization regions. The results are robust after various specifications of variables, possible endogeneity issues, and sub-samples are considered. •There is a U-shaped relationship between economic policy uncertainty (EPU) and corporate financialization.•The relationship is stronger for non-SOEs, firms with lower financing constraints, or located in lower marketization regions.•Investor sentiment serves as the mediating link between EPU and corporate financialization.•The influence of EPU on corporate financialization has different performances in different economic periods.